2012
DOI: 10.1021/ja3053865
|View full text |Cite
|
Sign up to set email alerts
|

Racemization of a Chiral Nanoparticle Evidences the Flexibility of the Gold–Thiolate Interface

Abstract: Thiolate-protected gold nanoparticles and clusters combine size-dependent physical properties with the ability to introduce (bio)chemical functionality within their ligand shell. The engineering of the latter with molecular precision is an important prerequisite for future applications. A key question in this respect concerns the flexibility of the gold-sulfur interface. Here we report the first study on racemization of an intrinsically chiral gold nanocluster, Au38(SCH2CH2Ph)24, which goes along with a drasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(167 citation statements)
references
References 48 publications
8
157
0
Order By: Relevance
“…Coinagem etal nanostructures have received considerable interest owing to their unique physicala nd chemical behavior, [1][2][3][4][5][6][7][8][9][10] delivering promising buildingb locks for functional nanomaterials. Particularly,t he knowledge of stable gold clusters has been well developed leading to the understanding of both structural and electronic properties, [11][12][13][14][15][16][17][18] with promising applicationsi nb iomedicine, catalysis, and sensing, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Coinagem etal nanostructures have received considerable interest owing to their unique physicala nd chemical behavior, [1][2][3][4][5][6][7][8][9][10] delivering promising buildingb locks for functional nanomaterials. Particularly,t he knowledge of stable gold clusters has been well developed leading to the understanding of both structural and electronic properties, [11][12][13][14][15][16][17][18] with promising applicationsi nb iomedicine, catalysis, and sensing, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The energy barrier to interconversion of the enantiomers is low, so the cluster loses optical activity at at 40 8C. 202 This makes the cluster of limited use in asymmetric catalysis and as component of chiral sensors at temperatures above 40 8C. The problem can be solved by introducing one or two 1,1 Hbinaphthyl-2,2 H -dithiol substituents into the cluster.…”
Section: Methods For Determination Of the Structure And Propertiementioning
confidence: 99%
“…[101] Later calculations found that ac hiral arrangement of the two propellers could furtherl ower the energy, [102] which is ar esult of the minimization of steric stress between the staple motifs. [105] Qian et al [106] also performed an NMR spectroscopy analysis on the racemic Au 38 (SR) 24 (R = CH 2 CH 2 Ph) nanoclusters and observed an interesting diastereotopicity effect in the two geminal protons in each CH 2 of the SCH 2 CH 2 Ph ligands on thec hiral Au 38 (SR) 24 nanocluster (Scheme 1). The separated enantiomers showed normal opticala bsorption peaks at l = 490, 520, 560, 620, and 750 nm (Figure 5a), which are the same as the peaks of the racemic mixture.…”
Section: With An Biicosahedral Kernelmentioning
confidence: 99%